2019
DOI: 10.3390/ani10010002
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Ammonia Affects Myofiber Development and Lipid Metabolism in Growing Pig Muscle

Abstract: Ammonia, an aerial pollutant in animal facilities, affects animal health. Recent studies showed that aerial ammonia negatively impacts meat quality but the mechanism remains unknown. To understand how ammonia drives its adverse effects on pig meat quality, 18 crossbred gilts were exposed to 0, 10 or 25 mg/m3 ammonia for 25 days. Ammonia exposure increased fat content in the Longissimus dorsi muscle, and meat color got lighter after 25 mg/m3 ammonia exposure. Analysis of MyHC isoforms showed an increased MyHC I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…7 F). Our previous studies found that serum Gln increased until aerial ammonia reached 35 mg/m 3 ( Tang et al., 2019 , 2020 ). These findings suggest the biosynthesis of Gln is favored at a high level of ammonia exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…7 F). Our previous studies found that serum Gln increased until aerial ammonia reached 35 mg/m 3 ( Tang et al., 2019 , 2020 ). These findings suggest the biosynthesis of Gln is favored at a high level of ammonia exposure.…”
Section: Discussionmentioning
confidence: 97%
“…We found that exposure to 35 mg/m 3 aerial ammonia activated the mammalian target of rapamycin (mTOR) pathway, consequently up-regulating genes involved in lipogenesis and down-regulating lipolysis genes in the muscle of pigs ( Tang et al., 2020 ). In contrast, aerial ammonia below 25 mg/m 3 has no such effect ( Tang et al., 2019 ). Interestingly, serum and muscular branched-chain amino acids (BCAA, including valine, isoleucine and leucine) were increased by high ammonia exposure when the mTOR pathway was activated ( Tang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…HDL is the only lipoprotein that transports cholesterol from peripheral tissues to the liver [ 31 ]. Tang et al [ 32 ] showed a decreased in the concentration of serum apoA1. Similarly, Sa et al [ 21 ] found that ammonia can significantly increases the level of serum HDL, de novo fat synthesis and cholesterol transportation in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The key function of LDL is transportation of cholesterol to cells throughout the body [35]. Tang et al [32] found that the concentration of apoB was increased when broilers were exposed to ammonia, indicating that ammonia affect lipid metabolism. In rabbits, low-grade inflammation and fat deposition have been known to negatively impact growth [36].…”
Section: Plos Onementioning
confidence: 99%
“…catabolism by suppressing the expression of BCAA catabolismrelated enzymes (unpublished data). Attractively, the type of skeletal myofiber, especially increased myosin heavy chain (MyHC) IIx or decreased MyHC I, was notably altered after aerial ammonia exposure, which indicated that the metabolic type of skeletal muscle changed from oxidative to glycolytic type (16,17). However, the specific mechanism that aerial ammonia jeopardizes animal health, causing metabolic disorder, is still unclear.…”
Section: Introductionmentioning
confidence: 99%